1998
DOI: 10.1046/j.1365-3024.1998.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12 and the host response to parasitic helminths; the paradoxical effect on protective immunity and immunopathology

Abstract: In general, helminth infections are associated with the development of dominant Th2-mediated immune responses which may be host protective but can also be the cause of immunopathology. Interleukin 12 (IL-12) is known to be a potent inhibitor of Th2 immune responses and as such it might be expected to have an important modulatory role in helminth-induced immune responses. In this review, we discuss the effect of IL-12 on susceptibility to infection, protective immunity and immunopathology, in the context of exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…Nevertheless, taken together, these findings demonstrate that the Th1-type response induced via the STAT4-dependent signaling pathway is essential for the control of cysticercosis, whereas a Th2-type response is detrimental and enhances susceptibility to the disease. Consistent with our observations, other studies using a radiation-attenuated vaccine with IL-12 as an adjuvant have also shown that a Th1-like response can mediate protective immunity against certain parasitic helminths, such as Schistosoma (26). Importantly, we found that CD4 ϩ cells were the main source of the cytokines analyzed (Table 1), with the exception of IL-10 in STAT4…”
Section: Stat4supporting
confidence: 92%
“…Nevertheless, taken together, these findings demonstrate that the Th1-type response induced via the STAT4-dependent signaling pathway is essential for the control of cysticercosis, whereas a Th2-type response is detrimental and enhances susceptibility to the disease. Consistent with our observations, other studies using a radiation-attenuated vaccine with IL-12 as an adjuvant have also shown that a Th1-like response can mediate protective immunity against certain parasitic helminths, such as Schistosoma (26). Importantly, we found that CD4 ϩ cells were the main source of the cytokines analyzed (Table 1), with the exception of IL-10 in STAT4…”
Section: Stat4supporting
confidence: 92%
“…In the context of protective immunity, we recently demonstrated that the high level of Th1-mediated protection (60 to 70%) induced in C57BL/6 mice by the radiation-attenuated (RA) vaccine model of murine schistosomiasis is dependent upon the presence of endogenous IL-12 (1,46). Moreover, administration of exogenous recombinant IL-12 during the first few days after vaccination leads to elevated levels of protection, concurrent with increased levels of Th1-associated humoral and cell-mediated immune responses (1,65,66).…”
mentioning
confidence: 99%
“…Similarly, ®larial parasites selectively induce Th2-type responses, but such dominant reactivity contributes to immunopathologic symptoms, such as ®laria-induced airway hyperresponsiveness (12). The pathogenesis of disease caused by Schistosoma infection also appears to be a Th2-mediated process, while Th1-type cytokines reduce immunopathologic disorder and promote protective immunity (13). From these investigations, we may conclude that pregnancy, by its selective induction of a Th2-promoting environment at the prenatal age, leading to prenatal sensitization and subsequent activation of Th2-type responses in neonates, may support protective immunity against intestinal helminth parasites, but such expression of immunity may also predispose to chronic infections and immunopathogenesis in ®lariasis and schistosomiasis.…”
mentioning
confidence: 99%